Anthropometric characteristics of rural elderly females in Malaysia - Yassin, Zaitun; Terry, Rhonda Dale (Gordon and Breach Science Publishers, 1991)
Selected anthropometric measurements were examined for 305 Malay females age 55 and older from selected rural villages in Malaysia. Although height and indicators of stature were similar to elderly Asian females living in similar environments, the Malay females were comparatively heavier with more body fat. Age was negatively and significantly related to changes in standing and sitting heights, arm span, body weight, body mass index, waist and hip circumferences, upper arm and arm muscle circumferences, mid‐arm muscle area, triceps skinfolds, and mid‐arm fat area. These age‐related changes may be a function of biological, secular, or methodological variation. Both underweight and obesity appear to be prevalent, and waist‐hip ratio trends indicate that excess body fat is preferentially deposited in the abdominal region. Such obesity trends may be contributing to the current rise in chronic disease death rates in Malaysia.